Dear Miloš: Bohuslav Martinů´s letters to Miloš Šafránek - Zouhar, Vít (Univerzita Palackého v Olomouci, 2020)
The monograph consists of a set of correspondence with Miloš Šafránek, a Czech diplomat, music journalist, Martinů's biographer, and a promoter of his work. The volume contains the diplomatic transcriptions of 168 letters, six postcard, five postal cards, one telegram, and one lettercard from the period of 1928-1959. The vast majority of the correspondence is unilateral, addressed to Šafránek, only two of the items were sent by Šafránek.
Keywords: Výtvarné techniky